Star wars. Return of the Jedi [videorecording (Blu-Ray)] - Hamill, Mark; Fisher, Carrie; Ford, Harrison, 1942-; Williams, Billy Dee, 1937- (LucasFilm, 2019)
In the epic conclusion of the saga, the Empire prepares to crush the Rebellion with a more powerful Death Star while the Rebel fleet mounts a massive attack on the space station. Luke Skywalker confronts Darth Vader in a final climactic duel before the evil Emperor.